Results of monitoring hail-damaged soybean crops - N. I. Zaitsev; V. Yu. Revenko; E. G. Ustarkhanova (Аграрная наука Евро-Северо-Востока, 2021)
Studies of the impact of hailstorm on the productivity of soybean agrocenoses were carried out in 2020. Hail damaged and undamaged areas sown with the same soybean variety or sample have been compared. The analysis was carried out on 60 variants (varieties and samples). The aim of the studies was to assess yield losses due to the following factors: reduced density of agrocenosis, leaf surface defoliation, damage to plant stems, weather conditions during the rest of the growing season after the hailstorm. It has been established that hail precipitation negatively affected the productivity of all damaged areas, regardless of the phenotype and ripeness group of varieties and samples. Defoliation of the most part of the leaf surface (from 70 to 80 %) and stems breaks led to decrease in the average yield in nurseries of preliminary and competitive variety testing from 1.85 t/ha to 1.34 t/ha (by 27.6 %), in seed and industrial sowings – from 2.04 to 1.53 t/ha (by 25.0 %). The average height of undamaged plants was 92.5 cm before harvesting, and 67.4 cm for damaged plants. Phenological observations showed that the closer to the end of the growing season the soybean crops are damaged by hail, the more negative the results. No plant lodging was observed at any of the damaged areas. There were no diseases affecting soybean agrocenoses, despite the significant accumulation of potentially pathogenic plant mass in the row spacing. This was probably due to dry and windy weather conditions during the rest of the growing season after the hailstorm.